2008
DOI: 10.1097/icb.0b013e3180eaa21b
|View full text |Cite
|
Sign up to set email alerts
|

Management of Optic Disk Pit–associated Macular Detachment With Tisseel Fibrin Sealant

Abstract: Our case series suggest that Tisseel fibrin sealant in conjunction with pars plana vitrectomy can be used successfully for management of optic pit disk-associated macular detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…There are several reports suggested sealing of the optic disc pit during surgery prevents passage of fluid into the subretinal spaces. Techniques designed to seal the optic disc pit include injection of autologous platelets; covering optic disc pit with ILM inverted flap; tissue glue pit sealing; autologus sclera pit clotting [21,22]. In turn the results of fenestration of internal retina (partial thickness retinotomy) show complete resolution of foveal fluid in 94% of eyes; with significantly improved of visual acuity in 56% of cases [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports suggested sealing of the optic disc pit during surgery prevents passage of fluid into the subretinal spaces. Techniques designed to seal the optic disc pit include injection of autologous platelets; covering optic disc pit with ILM inverted flap; tissue glue pit sealing; autologus sclera pit clotting [21,22]. In turn the results of fenestration of internal retina (partial thickness retinotomy) show complete resolution of foveal fluid in 94% of eyes; with significantly improved of visual acuity in 56% of cases [23].…”
Section: Discussionmentioning
confidence: 99%
“…110 Another novel method describes drainage of subretinal fluid through the optic disc pit to flatten the macula intraoperatively and then applying Tisseel fibrin sealant on the optic disc to seal it. 111 …”
Section: ' Optic Pitmentioning
confidence: 97%
“…However, Coleman et al also found that the glue was unable to seal large retinal tears and stressed that the tissue glue alone was not enough to ensure permanent retinal reattachment 82. Al Sabti et al used Tisseel fibrin sealant to seal optic disc pit-associated macular detachment in two out of three patients for at least 3 years 83. This required patients to stay in prone position for 2 weeks postoperatively.…”
Section: Retina Surgerymentioning
confidence: 99%